Antimicrobial resistance, virulence gene profiles, and molecular epidemiology of enterococcal isolates from patients with urinary tract infections in Shanghai, China - Wu, Weiyi; Xiao, Shuzhen; Han, Lizhong; Wu, Qiong (Microbiology spectrum, 2025)
This study highlighted the critical need to understand Enterococcal strains causing UTIs in Shanghai, given their high prevalence. By assessing antimicrobial resistance profiles, virulence gene presence, and molecular epidemiology, the research offered valuable insights into the local epidemiology of Enterococcus faecalis and Enterococcus. faecium . Identifying linezolid-resistant strains, all of which carry the optrA gene, including the first report of ST300 in China and recognizing dominant MLST types, such as ST16 and ST179 for E. faecalis and ST78 for E. faecium , are vital for guiding treatment and addressing the challenges these infections present. The data emphasize the need for ongoing surveillance and customized therapeutic approaches to combat emerging resistance and virulence factors in Enterococcal UTIs.